2007
DOI: 10.1148/radiol.2422060133
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Hemorrhage in Asymptomatic Neonates: Prevalence on MR Images and Relationship to Obstetric and Neonatal Risk Factors

Abstract: Asymptomatic ICH following vaginal birth in full-term neonates appears to be common, with a prevalence of 26% in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
185
4
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 291 publications
(200 citation statements)
references
References 39 publications
8
185
4
3
Order By: Relevance
“…16 However, MRI revealed that asymptomatic SDH at birth is common. [17][18][19] Some studies report a prevalence as high as 50%, 20 although no study so far reports persistence of SDH present at birth beyond 4 weeks. 21 The purpose of this study was to review the incidence of SDH in newborns with congenital heart disease undergoing MRI brain scans as part of a perioperative research protocol and to explore the relationship between SDH and hypoxia.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…16 However, MRI revealed that asymptomatic SDH at birth is common. [17][18][19] Some studies report a prevalence as high as 50%, 20 although no study so far reports persistence of SDH present at birth beyond 4 weeks. 21 The purpose of this study was to review the incidence of SDH in newborns with congenital heart disease undergoing MRI brain scans as part of a perioperative research protocol and to explore the relationship between SDH and hypoxia.…”
Section: Resultsmentioning
confidence: 99%
“…The rate of asymptomatic neonatal SDH in published literature ranges from 8% to 45%. [17][18][19]21 One previous study of SDH in a much smaller cohort of newborns with congenital heart disease identified preoperative SDH in 11 out of 21 (52%). 20 It is usually suggested that these SDHs originate from tearing of the dura or bridging veins by molding of the cranium during birth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnant women were recruited from the outpatient obstetrics−gynecology clinics at the University of North Carolina hospitals and Duke University Medical Center. Exclusion criteria for mothers included major maternal illness or infection during pregnancy, and maternal diagnosis of a major psychiatric disorder; for neonates, exclusion criteria included chromosomal abnormalities, severe congenital abnormalities, major medical illness or infection, and abnormalities on MRI other than small intracranial hemorrhages that are common in neonates (38). Zygosity was determined with PCR short tandem repeat analysis of 14 loci on DNA prepared from buccal swab cell collection (BRT Laboratories).…”
Section: Methodsmentioning
confidence: 99%
“…ICH following vaginal delivery in full-term infants has been shown to have a prevalence as high as 26%, of which intraparenchymal hemorrhage has been shown to be the second most common cause, following subdural hemorrhage. 8 Symptomatic spontaneous intraparenchymal hemorrhage is thought to be extremely rare in full-term newborns and literature available on this is limited. Sandberg et al identified no underlying cause in more than 50% of fullterm neonates with spontaneous intracranial hemorrhage.…”
mentioning
confidence: 99%